A certain kind of mindful man. (2nd July 2016) - Brazier, David
ABSTRACT: The character and work of Carl Rogers is examined in the light of both the contemporary "utilitarian" mindfulness and the original Buddhist sense of the term mindfulness. A parallel is drawn between the way in which utilitarian mindfulness has been abstracted from traditional mindfulness and the way in which Rogers' own principle of empathy has been received in the psychotherapy world. In both cases the merits and drawbacks of ethical neutrality are considered. The issues of purposefulness and of ethics in relation to both types of mindfulness are highlighted. Rogers is presented as an exemplar of mindfulness whose work helps us to reflect upon its true meaning.